Assistance in Information Governance and Administrative Services for The Sukasari Village Government through A Laravel Framework-Based Website - Muhammad Ilham Riyadi; Mohamad Ikrom Arasid; Gilang Maulana Subaly; Rangga Vernanda; Teti Ainur Hotimah; Moehamad Riefky Anandhita; Muhamad Gia Galihleo (MOVE: Journal of Community Service and Engagement, 2026)
The transformation of village government services requires not only technological tools but also assistance that enables village officials to organize information and administrative processes systematically. This community service activity aimed to assist the Sukasari Village Government in strengthening public information governance and administrative services through a Laravel-based website. The service method consisted of four stages: needs identification and service-flow review, application design and development, assistance in website implementation and management, and black-box functional evaluation. The resulting website integrates village profiles, demographic information, village budget summaries, local potential, maps, contact information, and service hours with four administrative services: poverty certificates, domicile certificates, moving certificates, and arrival certificates. Residents can submit personal data and upload identity card and family card documents, receive an application code, and track the application status using the code and national identification number. The administrator panel provides statistical dashboards, search and filtering, document review, status updates, PDF letter generation, CSV exports, PDF reports, village information management, and password updates. Evaluation in the development environment indicated that the main functions operated according to the specified scenarios. This assistance activity produced a more organized and traceable service medium that can support public information disclosure in Sukasari Village.